PROFIL TOKOH WANITA DALAM KABA CINDUA MATO KARYA SYAMSUDDIN SUTAN RADJO ENDAH - Ninawati Syahrul (Widyariset, 2010)
Kaba is the legend of Minangkabau people. It is a great literature in Minang and it has an important role in Minangkabau society. In Minang, it put matrilineal term . It is an intercommunication with the kinship system that is adhered materilined community, it is very interesting to examine the existence of these female figures. This study aims to describe the profile of women in “Kaba Cindua Mato” especially in Minangkabau society. This research includes descriptive studies. The profile of women is reflected as in “Kaba Cindua Mato” those whose sense of responsibility in life. This study is expected to encourage women of Minangkabau, so, they do not forget the Minangkabau culture.